Screening for interstitial lung disease in systemic sclerosis: the diagnostic accuracy of HRCT image series with high increment and reduced number of slices. Issue 4 (25th November 2011) - Winklehner, Anna; Berger, Nicole; Maurer, Britta; Distler, Oliver; Alkadhi, Hatem; Frauenfelder, Thomas
Abstract : Objectives: The objective of this study is to assess diagnostic accuracy for the detection of interstitial lung disease (ILD) in image series with high increment and reduced number of slices in patients with systemic sclerosis (SSc). Methods: 45 patients with SSc underwent high-resolution CT (HRCT). Three series of secondary captures were reconstructed as follows: series 1, series with 10 mm increment and 1 mm slices; series 2, seven axial images with baso-apical gradient; series 3, three axial images were obtained at the apical, at the level of the carina and basal. The presence and extent of ILD, and the degree of diagnostic confidence were recorded. The effective dose for each image series was estimated. Standard HRCT was the standard of reference. Results: The prevalence of ILD was 55% (25/45). Diagnostic sensitivity and accuracy of series 1, series 2 and series 3 were 100% and 94.4%, 94% and 97.8%, 92% and 97.8%, respectively. The extent of ILD was underestimated in series 3 (p<0.05) and was comparable to the standard HRCT in series 1 and 2 (p>0.05). Estimated dose reduction was more than 90% in all image series. Conclusions: HRCT image series with low sampling rate allow an accurate detection of ILD with very-low-radiation dose, making this approach potentially valuable for screening in patients with SSc.